PERAN PARENT CHILD RELATIONSHIP PADA ORIENTASI SEKSUAL GAY - Amalia Novita Retaminingrum (Universitas Sarjanawiyata Tamansiswa, 2017)
This research is conducted to see the role of parent child relationship in gay. Parent child relationship is an interaction between parent and a child which is included three main aspects namely, parenting, attachment, and social learning. Every individual has sexual orientation or has interested to other, it could be the same sex or to the other opposite sex. The person who is interested to the same sex, called Homosexual. Homosexual could be divided by two, which is lesbian and gay. This research is conducted on gay or individual male who is interested to the same sex. This research uses qualitative approach with in-depth interview to six persons who is 20 up to 40 years old who has gay sexual orientation. The result of this research shown that three aspects in parent child relationship has a role to six gay. On the first aspect, it is found that abusive in parenting has a big influence in sexual orientation, as well as the second aspect, attachment, which has a role to sexual preference in gay. On the third aspect namely social learning has a role in a learning process with environment that has the same sexual orientation; in this case, it is strengthen the individual sexual orientation.